Roman epic : an interpretative introduction - Albrecht, Michael von. (Mnemosyne, Supplements, 1999)
The author's approach to Roman epic is interpretative; the reader is invited to study a choice of typical texts, from the beginnings to the end of Antiquity. Famous poets are given the attention they deserve, but also some minor authors are discovered as precious 'missing links' between the ages. Special heed is paid to intertextual relationships between different epochs, cultures, literary genres, linguistic and literary patterns. The book is meant for students and teachers of classical and modern literatures, but also for all those interested in the history of literary genres and cultural ideas.